From e-Commerce Overall Quality to e-Loyalty: A Purchase-centred Framework - Nur Azizi, Fakri Fandy; Aknuranda, Ismiarta; Tolle, Herman (Journal of Information Technology and Computer Science, 2020)
The e-commerce market becomes one of the markets with the most promising growth. A number of studies on e-commerce have been investigated, but only a little attention is paid to the factors that may create e-commerce customer loyalty, even though customer loyalty is one of the primary keys to improve the performance of e-commerce businesses. This research offers a conceptual model focused on purchases to investigate the factors that affect customer's loyalty and when it is formed. Specifically, this paper intends to examine the relationship between the e-commerce overall quality on the perceived usefulness, perceived value, satisfaction and trust. This paper also verifies the relationship between perceived usefulness, perceived value, satisfaction and trust in the e-loyalty. The method of online survey is used for the data collection. From 1457 of the distributed questionnaires, 960 were completed and returned, resulted 65.8 percent response rate. The data is then analyzed using the Structural Equation Modeling (SEM) method. The research findings contribute to filling the knowledge gap regarding the defining factors of customer loyalty which may help the e-commerce provider in developing e-loyalty to increase e-commerce profitability.